Extradigital glomus tumor: dermoscopic description and histopathological correlation, - Lucas Campos Garcia; Ethel Nunes de Sousa Fernandes; Natália de Paiva Sobreira; Flávia Vasques Bittencourt (Sociedade Brasileira de Dermatologia, 2022)
Abstract Glomus tumors are rare benign neoplasms arising from the neuromyoarterial structure called glomus body. They present as angiomatous papules, soft and painful, especially to cold and pressure. In general, they are solitary and affect the extremities, located mainly the subungual bed. Extradigital lesions are rare and can constitute a diagnostic challenge. This is the report of a patient with an extradigital lesion on the left arm, and its dermoscopic aspects, including angiomatous lagoons circumscribed by a pale halo, a structure not previously described in the two reports of extradigital glomus tumor with dermoscopic features, found in the literature.